BOD and COD Content of Leachate from Air Dingin Landfill, Padang City - Sonia, Sonia; Muhelni, Leila; Anwar, Hendra; Mukhtar, Dertha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Padang City is a large city with an area of 694.96 km² and a population of 941,639 in 2018. The waste generated in 2018 amounted to 1,313,342.7 m³ (Padang City Environmental Agency, 2018). Landfills produce a type of liquid known as leachate. Leachate is a hazardous liquid generated from the decomposition of both organic and inorganic waste at the Final Disposal Site (TPA) of waste. This liquid contains high concentrations of organic, inorganic materials, and heavy metals that have the potential to contaminate groundwater, rivers, and surface water. This study aims to analyze the quality of leachate based on the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) parameters as the main indicators of organic pollution. Samples were taken from the outlet pond of the Air Dingin TPA in Padang City, then brought to and tested at the Andalas University Water Laboratory. The results showed a COD value of 450.4 mg/L and a BOD value of 250 mg/L. These values far exceed the quality standards established in the Minister of Environment Regulation No. 59 of 2016 concerning Wastewater Quality Standards. This study indicates that leachate requires further management before being released into the environment.